ILUSI OPTIK DENGAN TEKNIK LUKIS PADA BUSANA PESTA SORE - Sandra Tami Abdulah; Katiah Katiah (Universitas Pendidikan Indonesia, 2017)
Selection of an optical illusion can be applied to the satin. Line from-line, blue color and orange color inspired by the tropical orange color. In the manufacture of clothing by applying an optical illusion to be applied with paint, paint used was the kind of the kind of painted silk screening of rubber. The painting used to get an optical illusion is a technique. From a motive for the line that gives the impression of an optical illusion is applied in clothes one piece dress to party the aftertoon with a model of one piece of knee length dress. The textile component used which is black satin as the main fabric and lining. This clothing intended for woman with vulnerable age 20 – 25 yers for afternoon party. The purpose of the preparation of the final task of this is to develop knowledge and skills that have been obtained during the lecture, the purpose of the other which reached the desaig and manufacturing clothing for the Education of fashion design. The benefits of the preparation of the final task of this is to develop creativity in fashion with a pattern of an optical illusion. The method of project based learning (PBL), with the support of the study literature.